A interface família-escola na inclusão de crianças com necessidades educacionais especiais: uma perspectiva ecológica - Pamplin, Renata Christian de Oliveira (2005)
This study was based on the assumption that the presence of resources in the home environment in addition to special educational practices can either favor or damage the socialization and learning of children with Special Educational Needs (SEN). The aim was to identify the resources and needs in the home context of children with SEN and verify the relationship of such aspects to the proposals for inclusion from conventional schools of a city in the interior of the state of São Paulo. Sixty-one caregivers of children with SEN (33 with handicap and 28 with failure at school) and a secretary of the Municipal Department of Education participated in the study. A documentary analysis, a semi-structured interview with the secretary, and two questionnaires Inventory of Home Environment Resources (HER) and Questionnaire about Family Needs (QFN) were the instruments used for collecting data, supplying the study with quantitative and qualitative information. The documentary analysis was important since it assisted in finding possible participants. The interview was analyzed according to preestablished categories. The questionnaires were statistically analyzed with the aim of verifying possible significant differences between the two groups of children, as well as the relative frequency of the resources and needs investigated. After examining the results of each instrument, the triangulation among them was calculated so that the theoretical premises originated from the bioecological perspective on human development enabled a systematic reading of the situation studied. The results indicated that political actions on the macrosystem has strongly influenced those situations lived in both microsystem and mesosystem, inasmuch as such actions can either make concessions on certain resources or determine the children s hours and interactions with their family. Differences in quantity of resources offered by the school were verified between children with handicap and children with school failure. The caregivers of both groups were shown to feel the need for information about the children s characteristics, and also about the supports and services of the community. In addition, it was verified the need for financial support to those families whose children present school failure. Therefore, it is possible to conclude that, even though the current municipality s proposal for Special Education aims at parental participation, it does not have, in practice, enough mechanisms and strategies for promoting family involvement, and so it has to review its offer of resources for children with SEN.